In-situ and ex-situ study of crystallization behaviour of magnetron sputtered Ni63Zr37 amorphous thin film. Issue 20 (18th October 2019) - Sahu, Bibhu Prasad; Chatterjee, Arya; Dutta, Amlan; Mitra, Rahul
ABSTRACT: The stages of crystallization of magnetron sputter-deposited Ni63 Zr37 film with mostly amorphous structure have been investigated by differential scanning calorimetry (DSC) and in-situ annealing at 300°C by use of heating stage on a high-resolution transmission electron microscope (HRTEM). These results have been further confirmed by grazing incidence X-ray diffraction analyses of thin film specimens annealed ex-situ at 300°C for various durations. The temperature for crystallization found by DSC has been found to increase from 371°C to 434°C with an increase in heating rate from 3°C/min to 10°C/min, and the apparent activation energy for amorphous to crystalline transformation has been found as ∼260.2 kJ/mol from the Kissinger plot. Studies on HRTEM using in-situ heating stage have shown the crystallization to occur on annealing at 300°C for ∼10 min. Crystallization at a temperature lower than that found by DSC is attributed to structural relaxation with reduction of free volume due to thermal activation. It has been observed that Ni3 Zr forms first due to its large negative enthalpy of formation, and is followed by the formation of Ni-rich solid solution (Niss ) grains. HRTEM studies have shown grain rotation with the formation of partial dislocations at Ni3 Zr-Niss interfaces as well as twinning followed by detwinning with dislocation formation in the Niss matrix possibly to reduce the interfacial energy.